Three-dimensional investigation of fragment distribution in Al – 7wt.% Si solidified in microgravity. (15th May 2023) - Abou-Khalil, L.; Thompson, Z.; Reinhart, G.; Stan, T.; Sturz, L.; Zimmermann, G.; Voorhees, P.W.; Mangelinck-Noël, N.; Nguyen-Thi, H.
Abstract: Three-dimensional (3D) reconstruction of the microstructure of Al – 7 wt.% Si samples solidified in microgravity conditions on board of the International Space Station was obtained from serial-sectioning images. The main objective was to quantify the number of dendrite fragments issued from the solidification process in absence of buoyancy force and with motionless dendrite fragments on contrary to ground-based experiments. The results show that the number of fragments strongly depends on the dendrite network configuration. More fragments are observed in the sample containing several dendrites with different orientations compared to a sample with well-aligned dendrites. Moreover, it has been found that the highest number of fragments is mainly located in the region corresponding to an incipient grain boundary where dendrites with different orientations compete. Indeed, in this region solute accumulates and the microstructure is finer which is more prone to fragmentation of dendritic arms growing in this region. Thus, a mechanism that leads to the formation of dendrite fragmentation is identified: dendrite misorientation during solidification. Graphical abstract: Image, graphical abstract